Ecohydrological disturbances associated with roads: Current knowledge, research needs, and management concerns with reference to the tropics - Wemple, Beverley C. (2018)
Roads are a pervasive form of disturbance with potential to negatively affect ecohydrological processes. Some of the most rapid growth in road networks is occurring in developing countries, particularly in the tropics, where political agendas are often focused on strengthening the economy, improving infrastructure, bolstering national security, achieving self‐sufficiency, and increasing citizen well‐being, often at the expense of the environment. We review what is known about road impacts on ecohydrological processes, focusing on aquatic systems, both temperate and tropical. We present seven cases that represent the broader trends of road development and impacts in tropical settings. Many of these process dynamics and impacts are not different from those experienced in temperate settings, although the magnitude of impacts in the tropics may be amplified with intense rainfall and lack of best management practices applied to road construction/maintenance. Impacts of roads in tropical settings may also be unique because of particular organisms or ecosystems affected. We outline a set of best practices to improve road network management and provide recommendations for adopting an agenda of research and road management in tropical settings. Importantly, we call for incorporation of transdisciplinary approaches to further study the effects of roads on ecohydrological processes in the tropics. Specific emphasis should also be placed on collaboration with governments and developers that are championing road development to help identify the drivers of road expansion and thresholds of negative impact, as well as methods of sustainable road construction and maintenance.